Amplified DNA in Streptomyces fradiae. - Fishman, S E (1983)
A spontaneous mutant of Streptomyces fradiae contained an amplifiable unit of DNA with a sequence length of approximately 10.5 kilobases that was amplified to approximately 500 copies per chromosome. The amplified DNA appears to be cryptic. SalI fragments of the amplified DNA were cloned into Escherichia coli to construct a restriction map and characterize the amplified DNA. The amplified DNA contained tandem repeats of the amplifiable unit of DNA. The unit had an average base composition of 71% guanine plus cytosine, similar to the chromosomal DNA of Streptomyces species. At least a portion of the amplifiable unit of DNA was present at a low copy number in the wild-type strain. The phenotype of amplified DNA was designated Ads1SF for amplified DNA sequence 1 in S. fradiae.